Improving Bank Employee Performance through Motivation, Work Discipline and Work Environment - Yuli Artha Ratna Wulandari; Mokh. Natsir; Harianto Respati (Trescode Green Organization, 2024)
Efforts to improve employee performance at Bank Rakyat Indonesia (BRI) Magetan Regency Branch require proper processing of human resources to achieve the desired performance in line with expectations. Factors influencing employee performance include motivation, work discipline and work environment; these factors are mutually supportive in producing better employee performance. This research aims to analyze the influence of motivation, work discipline and work environment on employee performance at BANK BRI Magetan Regency Branch, both simultaneously and partially. This research also wants to analyze which variables, such as motivation, work discipline, and work environment, influence employee performance at BRI Bank Magetan Regency Branch. The type of research used is explanatory research. The research population was all first officer employees of the Indonesian Air Force at BRI Bank Magetan Regency Branch, namely 76 employees. Considering that the population is a manageable size, census research is used. Namely, all first officer employees at BRI Bank Magetan Regency Branch will be research respondents. The analysis method uses multiple linear regression and hypothesis testing. The research results show that motivation, work discipline and work environment affect the performance of first officer employees at BRI Bank Magetan Regency Branch, both simultaneously and partially. Furthermore, this research identified that work motivation has a dominant influence on employee performance at the BRI Bank Magetan Regency Branch.